PENGAWETAN KAYU AGATHIS, BUNGUR, KARET, DAN TUSAM DENGAN METODE PENCELUPAN - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1988)
This paper  deals with  a study  on a momentary  dipping  of freshly  sawn wood  for short periods  in a solution  of  33% boric  acid equivalent (BAE)  and  33% BFCA  preservative  at ambient   temperature,   followed by  one,  two,  three  and  four weeks  of  diffusion storage.  Boron  penetration were  then  calculated  and analyzed.  Results  of the study  reveal that  timber species  and  preservatives   do  not  any  significant   effect,   but  diffusion periods   show  highly  significant   effect to  boron penetration.   Boron  penetration   seemed  is normally   with  the  increas in diffusion storage period. Diffusion  storage of four weeks  for  all timber   tested  in  this  experiment  shows  relatively  good  results, so that  diffusion storage periods  for  four weeks  may  be recommended.